Program Pemutihan Pajak Kendaraan Bermotor Dalam Meningkatkan Penerimaan PAD Provinsi Jawa Barat Di Kantor Bersama Samsat Kawaluyaan Tahun 2023 - Nurhajati, Yati; Rizky Nurmulyani (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
One of the ways regional governments can increase local revenue (PAD) is by increasing the target for revenue collection from Motor Vehicle Tax (PKB). This research aims to find out how big the contribution of the motor vehicle tax reduction program is in increasing the local revenue (PAD) of West Java Province at the Kawaluyaan Samsat Joint Office. The research method used is a quantitative descriptive method, which explains or describes the state of West Java Province PAD in relation to income from motor vehicle tax at the time the whitening program was held, as well as identifying the obstacles faced in implementing the motor vehicle tax Bleaching program and the solutions offered by Samsat. The data used in this research was obtained from the results of evaluations, interviews and data collected at the Kawaluyaan Samsat Office for the period July - December 2023. The results of the analysis and discussion show that during the Bleaching program, and based on the Regional Tax Contribution Level Indicator of the Minister of Home Affairs Decree No. 690,900,327, motor vehicle tax revenue in the Kawaluyaan Samsat made a significant contribution to West Java's PAD. Because its contribution is in the very good category because it is in the 60% range.